OPTIMIZING GOLDEN PERIOD THROUGH EARLY DETECTION OF LANGUAGE SKILLS AND MULTILANGUAGE STIMULATION - Budiati Budiati; Dewi Rosnita Hardiany; Siti Haryani (PHILOSOPHICA Jurnal Bahasa, Sastra, dan Budaya, 2021)
The golden period is believed to be the most important period in the growth and development of children in which the brain is developed maximally. Early detection is needed to know the children’s competence and with accurate stimulation, this period can be optimized. Multilanguage stimulation is regarded to be one of the best stimulations to optimize language skills during the golden period. This study aims to find out how early detection and multilanguage stimulation can optimize the golden period. This study was descriptive qualitative research with 9 toddlers aged 1-5 years old and their mothers as the sample. The data were collected with Pre-screening Developmental Questionnaire (PDQ) to get the data of toddlers’ growth and development, and using a questionnaire to get the data of Multilanguage stimulation. From the study, it is found that most of the respondents (88.9%) have good development and only a respondent (11.1%) has a development defect. Whereas, in the multilanguage stimulation it is found that all respondents learned more than one language at the same time. However, most respondents only can use the second and third language little; they use it mix or switch with their mother tongue. They use code-mixing and code-switching with their mother tongue. It can be concluded that early detection is very important in stimulating children’s competence. The children’s language competence however is interfered with by several factors which one of which is accurate stimulation. Multilanguage stimulation will work well if there is a consistency of the surrounding in giving the stimulation.